Visual Snow Syndrome as a Network Disorder: A Systematic Review - Klein, Antonia; Schankin, Christoph J. (Frontiers in Neurology, 2021)
Visual Snow Syndrome as a network disorder: a systematic review Aim: To introduce visual snow syndrome (VSS) as a network disorder by reviewing and interpreting the clinical, imaging and electrophysiological picture of the condition. Background: Patients with VSS suffer from a continuous visual disturbance resembling the view of a badly tuned analogue television and other visual, as well as non-visual symptoms. These symptoms can persist over years and do often strongly impact the quality of life. The exact prevalence is still unknown, but up to 2,2% of the population could be affected. Presently, there is no established treatment, and the underlying pathophysiology is unknown. In recent years there have been several approaches to identify the brain areas involved and their interplay to explain the complex presentation. Method: We collected the clinical and paraclinical evidence from the currently published original studies on VSS by searching PubMed using the following and related terms: visual snow syndrome, MRI, PET, functional neuroimaging, visual evoked potentials. Results: The clinical spectrum includes visual disturbances such as visual snow sensu structo, excessive floaters, palinopsia, nyctalopia, photophobia, and entoptic phenomena. There is also an association with other perceptual and affective disorders as well as cognitive symptoms. The studies that have been included in this review demonstrate structural, functional and metabolic alterations in the primary and/or secondary visual areas of the brain. Beyond that, results indicate a disruption in the precortical visual pathways and large scale networks including the default mode network and the salience network. Discussion: The combination of the clinical picture and widespread functional and structural alterations in visual and extra-visual areas indicate that VSS is a network disorder. The involvement of precortical visual structures and attentional networks might result in an impairment of “filtering” and prioritizing stimuli as top-down process with subsequent excessive activation of the visual cortices when exposed to irrelevant external and internal stimuli.